Carrier signal based sensorless control of electrically excited synchronous machines at standstill and low speed using the rotor winding as a receiver - Rambetius, Alexander; Ebersberger, Sebastian; Seilmeier, Markus; Piepenbreier, Bernhard (Power Electronics and Applications (EPE), 2013 15th European Conference, 2013)
This paper presents a new carrier signal based approach for motion sensorless control of electrically excited synchronous machines. In the case of permanent magnet synchronous machines sensorless control at standstill and low speed is mostly done by injecting a high-frequency voltage and evaluating the resulting current response. Hence, the stator is used as the transmitter and as the receiver of the carrier signal. The major drawback is that a magnetic saliency is mandatory. In the case of electrically excited synchronous machines the rotor voltage serves as an additional input to the system and the resulting field current as an additional, easy to measure, state variable. The presented approach makes use of this fact and uses the field winding as the receiver of a carrier signal, which is injected into the stator winding. Like this no magnetic saliency is mandatory in order to track the position. The new approach is compared to a well-known carrier signal based method, in which the stator works as the transmitter and as the receiver of the carrier signal. In this case a magnetic saliency is mandatory which differs from the saliency necessary for permanent magnet synchronous machines. The applicability of both approaches is proven in experiments. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEEAS.carrie
Keywords: Sensorless control; Synchronous motor; Traction application; Vector control

Carrier Signal Based Sensorless Control of Wound Field Synchronous Machines Using the Rotor Winding as the Receiver: Rotating vs. Alternating Carrier Signal - Piepenbreier, Bernhard; Rambetius, Alexander (PCIM, 2015)
UnivIS-Import:2015-07-08:Pub.2015.tech.IE.LEEAS.carrie

Comparison of carrier signal based approaches for sensorless wound rotor synchronous machines - Piepenbreier, Bernhard; Rambetius, Alexander (2014 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM 2014), 2014)
Wound rotor synchronous machines enable a large variety of approaches for carrier signal based sensorless control since the rotor voltage serves as an additional input to the system and the rotor current as an additional, easy to measure, state variable. Consequently it is possible to use the rotor winding either as the transmitter or as the receiver of a carrier signal. In these cases the mutual inductance between the d-axis and the rotor winding is of major importance. Moreover a rotor saliency can be evaluated if the stator is used as the transmitter and as the receiver of the carrier signal. If voltage injection is used, the rotor winding acts like a damper winding for the carrier signal and consequently the evaluated saliency differs from the saliency which is utilized for sensorless control of permanent magnet synchronous machines. Carrier current control on the other hand offers the possibility to evaluate a magnetic saliency regarding the inductances in the d-and q-axis. This work provides a detailed review of the aforementioned approaches and analyses the prerequisites. In addition to this the different approaches are made comparable in terms of signal-to-noise ratio and cross saturation. This is done by introducing suitable intensity terms. With the help of identified parameters the most promising approach for the investigated machine is found. Experimental results confirm the validity of the comparison. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.compar_2
Keywords: electrically excited synchronous machine; high frequency injection; sensorless control; traction motor; wound field synchronous machine; wound rotor synchronous machine

Comparison of the Resistance- and Inductance-Based Saliency of a PMSM due to a Short-Circuited Rotor Winding - Graus, Johannes; Rambetius, Alexander; Hahn, Ingo (International Power Electronics Conference - ECCE Asia (IPEC 2014), 2014)
Sensorless position estimation based on signal-injection methods always requires a resistance- or inductance-based anisotropy. Therefore, a short-circuited electrical winding can be attached on the rotor. As will be derived in this paper, this method leads to both a resistance- and inductance-based saliency. By an experimental test setup, both saliencies are analyzed and compared towards their accuracy and frequency-dependence. Thereby, for the resistance-based saliency a characteristic behavior is found that can be explained by the interaction between the rotor winding and the eddy current effect. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.compar
Keywords: Eddy currents; interior permanent magnet (IPM) motor; ringed pole; sensorless control

Lagegeberlose Regelung der elektrisch erregten Synchronmaschine - Rambetius, Alexander (ECPE Cluster-Seminar, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.lagege

Modeling of Wound Rotor Synchronous Machines considering Harmonics, Geometric Saliencies and Saturation induced Saliencies - Rambetius, Alexander; Luthardt, Sven; Piepenbreier, Bernhard (International Power Electronics Conference - ECCE Asia, 2014)
Advanced control techniques for wound rotor synchronous machines need precise machine models. Often a simple fundamental wave model is used to design the control algorithms. Using such a model, it is not possible to account for non-ideal effects that distort the control algorithm. Therefore a general machine model is derived by extending classical winding function theory. This analytical machine model considers higher harmonics as well as geometric saliencies and saturation induced secondary saliencies and leads to new insights for wound rotor synchronous machines. Firstly it is shown that, under certain conditions, the stator slots induce higher harmonics in the rotor winding. Moreover cross saturation effects are described. Last but not least the machine model provides information about the origin of certain harmonics and about their phase depending on saturation. The suggested machine model is verified experimentally by measurement results. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.modeli
Keywords: EESM; harmonics; saturation; synchronous motor; winding function theory; wound rotor synchronous machine

Sensorless Control of Electrically Excited Synchronous Machines for Automotive Traction - Rambetius, Alexander (2014 Shanghai International New Energy Car Cooperation Conference, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.sensor_37

Sensorless Control of Wound Field Synchronous Machines for the whole Speed Range - Piepenbreier, Bernhard; Rambetius, Alexander (PCIM, 2015)
UnivIS-Import:2015-07-08:Pub.2015.tech.IE.LEEAS.sensor

Sensorless control of wound rotor synchronous machines using the switching of the rotor chopper as a carrier signal - Rambetius, Alexander; Piepenbreier, Bernhard (IEEE International Symposium on Sensorless Control for Electrical Drives and Predictive Control of Electrical Drives & Power Electronics (SLED-PRECEDE 2013), 2013)
Wound rotor synchronous machines open up new possibilities in carrier signal based sensorless control since the rotor voltage serves as an additional input to the system and the field current as an additional, easy to measure, state variable. Approaches for sensorless control of PMSMs use the stator as the transmitter and as the receiver of the carrier signal. A new alternative for wound rotor synchronous machines is to use the field winding as the transmitter and the stator as receiver. Since the field inductance is usually very large, a signal injection into the rotor is not reasonable because large rotor voltages are obligatory to create detectable stator currents. Therefore the presented approaches make use of the switching of the dc-field chopper as a carrier signal. Two methods are compared: The first method evaluates the stator currents in rotor fixed coordinates using a tracking observer. The second one uses the stator currents in stator fixed coordinates to directly compute the rotor position. Both methods consider cross saturation effects. In contrast to approaches for carrier signal based sensorless control of PMSMs no differential magnetic saliency is mandatory. Moreover no additional signal injection is necessary. Experimental results prove the performance of the proposed methods. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEEAS.sensor
Keywords: carrier signal injection; DC-excited synchronous machine; electrically excited synchronous machine; externally excited synchronous machine; sensorless control; synchronous motor; wound rotor synchronous machine

Speed Estimation and Compensation for Harmonics in Sensorless Wound Rotor Synchronous Machines. - Rambetius, Alexander; Luthardt, Sven; Piepenbreier, Bernhard (IEEE International Symposium on Sensorless Control for Electrical Drives (SLED 2014), 2014)
The conventional approach to control synchronous machines without a motion sensor in medium and high speed range is model-based and evaluates the electromotive force (EMF). In this case the information about the rotor position is included in the fundamental wave of the EMF and therefore the presence of harmonics will distort the estimation result. In order to compensate for harmonics information about their frequency is a prerequisite. In the case of wound rotor synchronous machines it is possible to obtain an accurate estimate of the speed by tracking the effect of the stator slots in the rotor current. For the rotor winding the stator slots represent a position dependent reluctance variation and therefore the rotor current will contain a harmonic component which is related to the rotor speed. The frequency of this harmonic component is tracked using an adaptive tracking filter and is then used to compensate for harmonics in the stator currents. The compensation is done by using adaptive resonant controllers. The suggested approach is verified experimentally by a highly utilized machine which is designed for automotive traction applications and features an extra-low voltage DC-link. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.speede
Keywords: electrically excited synchronous machine; harmonics; sensorless control; stator slots; traction motors; wound field synchronous machine; Wound rotor synchronous machine